2018
DOI: 10.25273/jipm.v7i1.2965
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self Regulated Learning to Mathematics Critical Thinking Ability on 3D-Shapes Geometry Learning using Geogebra

Abstract: <p>3D-Shapes Geometry is one of the subjects material that must be taught to students in Mathematics Education Program, which later after graduation will become a math teacher. Learning 3D-Shapes Geometry has relevance to the mathematics critical thinking ability. Students who have the ability to think critically can think rationally by collecting information as completely as possible. Learning that can stimulate the ability of critical thinking should be learning in which there are activities that are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
4
0
6
Order By: Relevance
“…This can be seen from the very small effect size area but its position is to the right of the vertical line. In this study, it was stated that self-regulated learning contributed 45.7% to critical mathematical reasoning, while 45.3% of mathematical critical reasoning is influenced by other variables (Hidayati & Kurniati, 2018).…”
Section: Figure 3 Funnel Plotmentioning
confidence: 79%
“…This can be seen from the very small effect size area but its position is to the right of the vertical line. In this study, it was stated that self-regulated learning contributed 45.7% to critical mathematical reasoning, while 45.3% of mathematical critical reasoning is influenced by other variables (Hidayati & Kurniati, 2018).…”
Section: Figure 3 Funnel Plotmentioning
confidence: 79%
“…Several other studies have also shown that GeoGebra is very effective in learning mathematics. Hidayati and Kurniati [43] discovered that learning using GeoGebra-assisted Spatial Geometry teaching materials is capable of improving students' critical thinking skills. Dwijayani [44] reported that learning using GeoGebra improves students' mathematical problem-solving abilities and stimulates students' creative thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini bertolak belakang dengan hasil penelitian Bell dan Pape (2014) yang menyebutkan bahwa scaffolding dan SRL saling berkaitan satu sama lain. Beberapa hasil penelitian memaparkan hubungan antara scaffolding dengan SRL (Perry et al, 2008), SRL dengan kemampuan berpikir kritis (Hidayati & Kurniati, 2018), dan scaffolding dengan kemampuan berpikir kritis (Kim et al, 2013). Namun hasil penelitian-penelitian tersebut menunjukkan bahwa antar variabel memberikan hubungan yang positif.…”
Section: Gambar 1 Pembelajaran Menggunakan Geogebra Onlineunclassified